Social Responsibility of Public Relations Practice to Involve Stakeholders - Ašanin Gole, Pedja (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
The erosion of social trust, brought about by the global financial and economic crisis, is directly related to the fall in the level of public communication and in this context also all those involved in the system of public communication, including practitioners of public relations. Corporate social responsibility implies that organizations must take into account in its operations and involve stakeholders and the community. The organizational activities must be balanced with expectations, values ​​and norms of the stakeholders and the community. Social responsibility of managers and practitioners of public relations is reflected in the proactive efforts for participatory social culture and social good, which places the emphasis on the interests of the community. Even if the public relations of recent Slovenian history, sometimes used as a justification and legitimization of wild privatization, and we are witnessing a smaller or greater evasion of the principle of public accountability, openness, transparency, a two-way communication and stakeholder inclusiveness - all of those contributes to the erosion of the system of public communication - however, analysis of 52 examples of the mostly internationally awarded Slovenian communication programmes implemented in the period 2000-2014 (created in the form of case studies) show that the practice of Slovenian public relations, however, able to detect opportunities and effectively contribute to the effective stakeholder inclusivness and convergence to communities.